Polio Virus neutralizing antibody dynamics among Children In A North-Central And South-Western Nigeria State (2014)
Northern Nigeria accounts for the highest number of confirmed wild polio viruses globally. Transmission to neighboring countries is worrisome after the country failed to meet several deadlines for polio eradication. Most studies on neutralizing antibody have focused on the Northeastern and Northwestern regions. This study measured polio virus neutralizing antibody levels among children in North-central and South-western Nigeria. Children between the ages of 10 months and 13 yr were randomly selected from Abanishe-lolu Hospital Ilorin (North-central) and Oni Memorial and Adeoyo Hospitals in Ibadan (South-west) Nigeria. The alpha neutralization method was employed. Herd immunity was 1.4% in Ilorin, 36.6% in Oni Memorial Hospital, and 49.5% in Adeoyo Hospital. Out of 299 children studied, 49 (16.4%) children had no protection against all poliovirus serotypes while 100 (33.4%) were fully protected against all three serotypes. Five (7.9%) children in Ilorin and 5 (3.4%) children in Oni Memorial Hospital Ibadan had no detectable neutralizing antibody. A significant difference was observed (p=0.000) when the GMT against poliovirus 1, 2, and 3 was compared. A significant proportion of children were not fully protected. Sero-surveillance is recommended for effective monitoring of vaccination efforts to guide health policy formulators.